Unilateral Vocal Fold Paralysis and Voice Therapy: Predictors of Long-Term Quality of Life - Sousa, Francisco Alves de (2023)
To date, little is known about the long-term predictors of quality of life (QoL) in unilateral vocal fold paralysis (UVFP). The main objective of this study was to evaluate the predictors of long-term QoL in UVFP patients submitted to voice therapy (VT) exclusively. Data from patients diagnosed with UVFP who followed a VT program between 2013 and 2019 were reviewed. Video laryngoscopy (VL) records were obtained at the beginning and at the end of VT. To assess QoL, Voice Handicap Index 30 (VHI-30) score was assessed in three temporal frames: before voice therapy (pre-VT), at the last VT session (post-VT), and in the present (cur-VHI). A longitudinal analysis was performed regarding the evolution of QoL and the factors influencing QoL through time were analyzed. Seventy-eight percent of patients had iatrogenic UVFP. The mean time of follow-up after VT was 3.942 years (range 6 months-7 years). There was a significant improvement in QoL through all time points (F (2,88)=72.179, p<0.001), with VHI-30 decrease from the baseline pre-VT to post-VT(p<0.001) and from post-VT to cur-VT (p=0.0013). In the iatrogenic UVFP population, patients starting VT earlier showed better long-term QoL (p=0.023). UVFP patients with dysphagia at presentation showed significantly worse QoL in the late follow-up (p=0.016). Hence, iatrogenic UVFP patients beginning VT rapidly may show better QoL in the future. Also, our results suggest that dysphagia at UVFP onset may predict higher morbidity later in life.